2022
DOI: 10.1108/aeat-08-2021-0251
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of environmental effect factor and exergetic sustainability index with cuckoo search algorithm for a business jet

Abstract: Purpose The purpose of this paper is to create models that predict exergetic sustainability index (ESI) and environmental effect factor (EEF) values with high accuracy according to various engine parameters. Design/methodology/approach In this study, models were created to estimate ESI and EEF sustainability parameters in various flight phases for a business jet with a turboprop engine using the cuckoo search algorithm (CSA) method. The database used for modeling includes the various engine parameters (torqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…With nonlinear algorithm, R 2 of thrust modeling attends to 0.9996. Oruc et al [ 22 ] modeled exergetic indexes of turboprop engine using cuckoo search algorithm. For this aim, six inputs including torque, power, gas generator speed, air&fuel mass flows and air to fuel ratio were used.…”
Section: Introductionmentioning
confidence: 99%
“…With nonlinear algorithm, R 2 of thrust modeling attends to 0.9996. Oruc et al [ 22 ] modeled exergetic indexes of turboprop engine using cuckoo search algorithm. For this aim, six inputs including torque, power, gas generator speed, air&fuel mass flows and air to fuel ratio were used.…”
Section: Introductionmentioning
confidence: 99%
“…18 Since then, many authors have been applying the defined exergetic sustainability indices to assess various types of systems, including air conditioning systems, 19 gas turbine power plants, 20 etc. Very recently, Oruc et al 21 modelled the exergetic sustainability index (ESI) and environmental effect factor (EEF) of a business jet using a cuckoo search algorithm. The study was an attempt to automate the exergetic sustainability performance metrics for this type of system, and they concluded that the algorithm employed could help standardize the incorporation of sustainability assessment to jet designs.…”
Section: Introductionmentioning
confidence: 99%
“…Exergy-based methods have been affirmed capable in the literature of improving performance metrics of energy systems [17][18][19] Specifically, on environmental sustainability, exergetic methods have been applied to assess several types of energy systems such as air conditioning, 20 evaporative cooling plants, 21 gas turbine electricity plants, 22 and aircraft jet designs, 23 etc. Additionally, Maruf et al 24 demonstrated the applicability of the exergetic sustainability method for the assessment of power generation scenarios at a national level using the situation in Bangladesh as a case study.…”
Section: Introductionmentioning
confidence: 99%